Animal Disease and Financial Markets : A Stock Price Analysis in an Emerging Economy - Patil, Ameya Anil; Saha, Shantanu (Indian Journal of Research in Capital Markets, 2024)
Purpose : Abnormal events affected the whole of the economy or specific sectors. The research dwelled into one of such unexpected events, viz. animal disease outbreak. The basic purpose was to analyze its effect on the stock prices of the allied businesses. Methodology : We compared the stock prices of these companies during the two months of January 2021 and February 2021 to analyze the changes in returns and identify any potential abnormal (negative) returns during the bird flu outbreak. We collected stock price data for listed poultry companies on the National Stock Exchange (NSE) and Bombay Stock Exchange (BSE). Findings : The results revealed negative abnormal returns associated with the event for around one month. In fact, the next month even saw a bounce back in stock prices of larger companies. Practical Implications : The implications were useful for investors looking to make investment decisions concerning these stocks in the wake of such events. At the same time, the results provided insights for the promoters and managers of related businesses regarding shareholder wealth erosion during such events, reinforcing upon them the need for food safety measures and risk management strategies in this context. Originality : This study is the first of its kind in the Indian context to examine stock price reactions in the event of an animal disease outbreak, viz., bird flu.